Public sector shared services and the lean methodology: Implications on military organizations - Renato J. Lopes da Costa; Tiago Resende; Álvaro Lopes Dias; Leandro Pereira; José Santos (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
During the economic and financial crisis, private and public organizations were subject to a constant reduction in costs and resources. Public shared service models felt compelled to adopt the Lean methodology with the aim of reducing costs, reducing waste and increasing employee satisfaction with the provision of quality services. Against this background, this article aims to evaluate the impact of the implementation of Shared Services and the inherent benefits of lean management in the Military Store, Contact Center, Post Office and Internal Portal used by the Portuguese Air Force. Using a case study methodology, this study portrays the elimination of waste and the optimization of existing human and financial resources. After the implementation in 2015, it is still possible now to verify that there is some resistance to change, and the fact that we are dealing with a hierarchical organization justifies this disadvantage. The implementation and operation of all services in their entirety allowed the optimization of resources and the simplification of processes, resulting in the elimination of duplicate tasks.
Keywords: 650; lean methodology; lean tools; shared services; optimization